Clinicians’ perceptions for indicating and contra-indicating integrated treatment for SUD and comorbid PTSD, a vignette study - Germa Catherina Maria Nass; Leon Willem van Rens; Boukje Arnolda Gerdina Dijkstra (Substance Abuse Treatment, Prevention, and Policy, 2019)
Abstract Background Posttraumatic Stress Disorder (PTSD) is more common in patients with Substance Use Disorder (SUD) than in the general population. Although international guidelines recommend integrated treatment clinicians are still hesitant in offering integrated treatment and more concrete recommendations are needed. This study aims to contribute to a practice-based guideline through the exploration of practice-based decision criteria to determine the indication and treatment of SUD and PTSD. Methods A vignette study to explore the views of experienced clinicians on the treatment of SUD and PTSD. Results Thirty-one experienced clinicians working in Dutch addiction care facilities filled in 15 vignettes resulting in 465 scored vignettes. Respondents did not report any contra-indications for integrated treatment and the perceived relationship between SUD and PTSD was found to be an important factor in the indication of integrated treatment. Conclusions For integrated treatment to be offered to all eligible patients more training and schooling in trauma treatment and comorbid psychopathology is needed for all disciplines involved. Inpatient treatment options are necessary when patients need external support due to psychiatric or physical vulnerabilities. Further research into the effect of the relationship between SUD and PTSD on treatment execution and effectiveness is needed and can contribute to future treatment guidelines.